Collaborator training as a strategy for continuous improvement (GEON Journal (Management, Organizations and Business), 2019)
Training as a tool for continuous improvement that allows the collaborator to grow, is developed through two parts, an induction plan that must be able to start that new member's infatuation with the organization, providing a general and specific learning, in turn a training plan that leads to organizational development, based on needs, carried out in an orderly manner, evaluating their development and, above all, measuring the impact on strategic aspects
Keywords: training; induction; continuos improvement